FLOOD MANAGEMENT SYSTEM IN PAKISTAN - A., Zarmina,; Farooq, S.H.; S, Naeem (European Scientific Journal, ESJ, 2014)
Pakistan is prone to disasters and these disasters altogether cannot be stopped; however, their ill effects can be minimized through a pragmatic (Flood Management System). Year 2010 witnessed the unprecedented floods in Pakistan, which rose to the highest levels in the recorded history. Thereby, preparation in Disaster Management is a compulsion rather than a choice. The paper mainly focus on contours/underpinnings of flood 2010, however, cardinal aspects of role of various stake holders have been incorporated in the working paper. The data has been acquired through various sources to include reports, online databases, and policy document as result to analyze the overall scenario of the country and the provinces as well. Both the secondary/primary data and information has been used to understand existing flood management system of Pakistan in purview of Floods-2010, with a view to recommend suitable measures The analysis revealed that flood management requires deliberation both at national and local level. The decentralized mode of operation should be adapted from national to regional level in order to follow an integrated framework for bringing all stakeholders and victims together for developing an organized management system. The aim is to carry out analysis of existing flood management system of Pakistan in purview of Floods 2010, with a view to recommend suitable measures to enhance flood management capacity in Pakistan.